2001
DOI: 10.1097/00003246-200104000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Diaspirin crosslinked hemoglobin enables extreme hemodilution beyond the critical hematocrit

Abstract: DCLHb as a diluent allowed for hemodilution beyond the hematocrit value, determined "critical" after hemodilution with HSA (6.1% (1.8)%). Even at 1.2% hematocrit (hemoglobin, 4.7 g x dL(-1)) myocardial perfusion and function were maintained, although at the expense of peripheral tissue oxygenation. This discrepancy in regional oxygenation might be caused by a redistribution of blood flow favoring the heart, which is related to a disproportionate decrease of coronary vascular resistance index during hemodilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 29 publications
1
26
1
1
Order By: Relevance
“…Consistently, the value of Hb crit in the Roc group (2.4 ± 0.5 g/dl) is comparable to that described in paralyzed animals [13,15,16,17,18,19], while the values of Hb crit obtained in nonparalyzed animals are similar to Hb crit observed in the Sal group [4,12]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistently, the value of Hb crit in the Roc group (2.4 ± 0.5 g/dl) is comparable to that described in paralyzed animals [13,15,16,17,18,19], while the values of Hb crit obtained in nonparalyzed animals are similar to Hb crit observed in the Sal group [4,12]. …”
Section: Discussionsupporting
confidence: 87%
“…In several experimental studies, a decrease in Hb crit demonstrated that anemia tolerance is increased by (1) hypothermia (moderate reduction of body core temperature reduces total body O 2 demand [16]), (2) hyperoxic ventilation (bioavailability of physically dissolved O 2 is excellent in profound anemia [12,17,18]), (3) infusion of norepinephrine (stabilization of coronary perfusion pressure during hemodilution [13]), and (4) artificial O 2 carriers (maintenance of CaO 2 despite reduced hematocrit [19,20]). In contrast, anemia tolerance is decreased by (1) hypovolemia (reduction of microcirculatory O 2 supply), (2) profound anesthesia (pharmacologic reduction of the cardiac output response to hemodilution [21,22]) and (3) by coronary artery disease (reduced coronary flow reserve [23]).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of organ surface PO 2 using Clark-type electrodes have been established in several studies as a suitable instrument for assessing tissue oxygenation in a variety of organs (7,17,19,21). PO 2muc measurements require diffusion of O 2 through mucosal epithelial cells to the electrode were O 2 is consumed in a complex redox reaction (16).…”
Section: Discussionmentioning
confidence: 99%
“…After moderate hemodilution, the increase of CO and microvascular blood flow, due to reduced blood viscosity, maintained oxygen supply to the tissues. Sufficient oxygenation of the tissues is limited by the functional reserve of the heart, as at a given hematocrit an increase in cardiac output is needed to deliver oxygen needs 30,31 . However, continuing the progressive hemodilution regulatory mechanisms tend to fail, even with PFCOC emulsion combined with hyperoxia.…”
Section: Discussionmentioning
confidence: 99%